4D Printing: An Innovative Technology For Self-transforming Structures and Multidisciplinary Applications (Asian Journal of Pharmaceutics (AJP), 2024)
4D printing, an innovative technology merging conventional additive manufacturing with smart materials andexternal stimuli, empowers objects to undergo transformative processes over time, exhibiting qualities like selfsensitivity,self-assembly, and self-healing. This technology harbors the potential to reshape modern constructionpractices, aligning with the demand for autonomous, energy-efficient, and environmentally sustainablestructures. Furthermore, 4D printing proves valuable in medicine and aerospace. 4D printing can revolutionizeaerospace manufacturing and design by enabling the creation of smart, adaptive, and highly efficient componentsand structures that can enhance the performance, reliability, and sustainability of aerospace systems. In thedomain of conventional robotics, rigid materials such as metals, hard plastics, and ceramics are predominantlyemployed in the construction of robotics that can efficiently respond to a multitude of stimuli. Textiles offerself-sustainability, reduced material consumption, and enhanced adaptability. Despite challenges, 4D printingholds significant potential across various domains, urging substantial research and development efforts for itssuccessful integration.